2013
DOI: 10.1186/1472-6963-13-353
|View full text |Cite
|
Sign up to set email alerts
|

Nursing home staff’s views on residents’ dignity: a qualitative interview study

Abstract: BackgroundMaintaining dignity is an important element of end-of-life care and also of the care given in nursing homes. Factors influencing personal dignity have been studied from both nursing home residents’ and staff’s perspective. Little is however known about the way nursing home staff perceive and promote the personal dignity of individual residents in daily practice, or about staff’s experiences with preserving dignity within the nursing home. The aim of this study is to gain more insight in this.MethodsA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
57
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 25 publications
0
57
0
2
Order By: Relevance
“…In congruent with the findings of other studies, in current study patients' perception of dignity improved with increasing in patients' age. The findings of other studies showed that dignity violation is more prevalent among older people (Hall et al, 2009;Oosterveld-Vlug et al, 2013). However, it also has been reported that sense of dignity violation is more common among younger people due to importance of physical appearance, lack of job performance and control over life, early death, and a lesser time to achieve life goals (Calnan et al, 2004;Chochinov et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…In congruent with the findings of other studies, in current study patients' perception of dignity improved with increasing in patients' age. The findings of other studies showed that dignity violation is more prevalent among older people (Hall et al, 2009;Oosterveld-Vlug et al, 2013). However, it also has been reported that sense of dignity violation is more common among younger people due to importance of physical appearance, lack of job performance and control over life, early death, and a lesser time to achieve life goals (Calnan et al, 2004;Chochinov et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…, Oosterveld‐Vlug et al . ). Patients consistently report that they expect individualized, patient centred care delivered through a caring relationship between staff and patients where patients’ and their families’ views are considered and integrated into care (Attree , Woolhead et al .…”
Section: Introductionmentioning
confidence: 97%
“…One reason for the high ratings of the perception of personal acceptance could be that the older patients in this study were discharged from hospital and felt quite independent. Earlier studies suggest that patients who are particularly dependent on nurses’ assistance have impaired cognition or communication difficulties or feel a lack of personal acceptance (Moe et al., ; Oosterveld‐Vlug, Pasman, van Gennip, Willems, & Onwuteaka‐Philipsen, ) which in some circumstances has led to the danger of neglect or even mistreatment (Buzgova & Ivanova ).…”
Section: Discussionmentioning
confidence: 99%